Food waste in households: Children as quiet powerhouses. (June 2022) - Kansal, Monika; Ananda, Jayanath; Mitsis, Ann; Karunasena, Gamithri Gayana; Pearson, David
Highlights: Children often hold significant power around what food is purchased and eaten. Eating habits of children can interfere with parents' well-intentioned plans. Parents are conflicted with needing children to eat and their desire for healthy food. Supermarkets encourage impulse buying by targeting children with appealing promotions. Abstract: This study reports parents' perceptions about children's influence on the generation of household food by collecting qualitative data from 15 focus groups of Australian householders from five culturally diverse communities. Key findings include food over-purchase to some extent results from children applying pressure on their parents to impulse buy supermarkets promoted products, fussy eating behaviours, and frequently changing preferences. Children's selective eating behaviours and preferences also cause food over-preparation and over-provisioning by parents. This study also identified that campaigns promoting imperfect shaped fruit and vegetables tend to be less effective with children as they desire perfect shaped fresh produce. We also identified that migrant communities tend to face the added complication of balancing traditional food for adults with their children requesting Australian foods. Our research presents policy implications in identifying children as quiet powerhouses in Australian households and suggests the need for targeted interventions to change children's food behaviour. Additionally, parents need to mirror these interventions in their households to reinforce desired changes in their children's food behaviours. There is also an opportunity for supermarkets, local councils and government agencies to redesign their marketing campaigns to educate children and parents about reducing food waste.